2022
DOI: 10.1088/1748-605x/ac62e7
|View full text |Cite
|
Sign up to set email alerts
|

LBL assembly of Ag@Ti3C2T X and chitosan on PLLA substrate to enhance antibacterial and biocompatibility

Abstract: Poly L-lactic acid (PLLA) is a non-toxic, biocompatible degradable polymer material with excellent mechanical properties after molding. However, it faces challenges in the use of biomedical materials because of its intolerance to bacteria. Here, we use an easy-to-operate method to prepare a composite multilayer membrane: PLLA membrane was used as substrates to assemble positively charged chitosan and negatively charged Ag@MXene on the surface using the Layer-by-layer (LBL) method. The assembly process was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…A multilayer Ti 3 C 2 T x /chitosan/Ag coating formed via the self-assembly approach demonstrated outstanding antimicrobial properties, effectively reducing both Gram-negative bacteria ( P. aeruginosa ) and Gram-positive bacteria ( S. aureus ) by 99.9% [ 133 ]. Additionally, a poly(L-lactic acid) membrane assembled with positively charged chitosan and negatively charged Ag@Ti 3 C 2 T x exhibited a synergistic antimicrobial effect, resulting in growth inhibition rates of 91.27% against E. coli and 96.11% against S. aureus [ 134 ]. A sandwich-structured superhydrophobic composite film created using superhydrophobic Ti 3 C 2 T x and nanocellulose as raw materials via the LBL self-assembly method demonstrated excellent self-cleaning ability, water repellency, and durability, as well as high photothermal conversion capability and stability.…”
Section: Preparation Methodsmentioning
confidence: 99%
“…A multilayer Ti 3 C 2 T x /chitosan/Ag coating formed via the self-assembly approach demonstrated outstanding antimicrobial properties, effectively reducing both Gram-negative bacteria ( P. aeruginosa ) and Gram-positive bacteria ( S. aureus ) by 99.9% [ 133 ]. Additionally, a poly(L-lactic acid) membrane assembled with positively charged chitosan and negatively charged Ag@Ti 3 C 2 T x exhibited a synergistic antimicrobial effect, resulting in growth inhibition rates of 91.27% against E. coli and 96.11% against S. aureus [ 134 ]. A sandwich-structured superhydrophobic composite film created using superhydrophobic Ti 3 C 2 T x and nanocellulose as raw materials via the LBL self-assembly method demonstrated excellent self-cleaning ability, water repellency, and durability, as well as high photothermal conversion capability and stability.…”
Section: Preparation Methodsmentioning
confidence: 99%
“…Ag@MXene (Ag@Ti 3 C 2 T x composite) was prepared as described in our previous study [ 26 ]. First, Ti 3 AlC 2 powder was slowly added to the etching solution containing LiF and hydrochloric acid and stirred at 50 °C for 24 h. Then, it was washed with deionized water until pH = 6 and dried.…”
Section: Methodsmentioning
confidence: 99%
“…Ag/MXene could be used as a conductive and antibacterial component, resulting in hydrogels with good electrical conductivity and antibacterial activity (93% inhibition of S. aureus and 95% inhibition of E. coli ) and improved hydrogel elongation (580%). Wang et al [ 26 ] assembled positively charged chitosan and negatively charged Ag@MXene on the PLLA surface by the layer-by-layer self-assembly (LBL) method, and the growth inhibition of both E. coli and S. aureus under 808 nm NIR laser radiation was higher than that of pure MXene-PLLA membrane. In addition, MXene has good electrical conductivity and has made great progress in sensing.…”
Section: Introductionmentioning
confidence: 99%
“…30 It has been reported that MXene/metal heterojunctions have been constructed with a small amount of Ti 3 C 2 T x with abundant active groups as the substrate, and the chemical-photothermal synergistic effect improved the antibacterial effectiveness. On this basis, the synthesized MXene/Au, 31 MXene/Co, 32 MXene/CuS 33 and MXene/Ag 34 showed promising antibacterial activity.…”
Section: Introductionmentioning
confidence: 92%
“…30 It has been reported that MXene/metal heterojunctions have been constructed with a small amount of Ti 3 C 2 T x with abundant active groups as the substrate, and the chemical-photothermal synergistic effect improved the antibacterial effectiveness. On this basis, the synthesized MXene/Au, 31 MXene/Co, 32 MXene/CuS 33 and MXene/Ag 34 showed promising antibacterial activity. Metal-organic frameworks (MOFs) is a new type of composite porous material composed of metal nodes (metal ions or clusters) and organic ligands (bipedal or multipedal organic ligands), which has been widely reported in recent years due to their extraordinary properties.…”
Section: Introductionmentioning
confidence: 92%